Implementasi Evaluasi Pembelajaran Pendidikan Al Islam di Sekolah Menengah Atas Muhammadiyah - Ahmad Fauzi; Nurul Latifatul Inayati (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
The purpose of this study is to identify the basic ideas of evaluation and their consequences for the assessment of Islamic religious education taught in schools. Qualitative techniques and literature review methods were used in this work. The findings of the discussion show that measurement and assessment shape evaluation. Because it is included in the learning phase, evaluation plays an important strategic role in the learning environment. The aim is to evaluate the efficacy and efficiency of the learning system. Assessment of learning programs, learning activities, and learning outcomes are included in the discussion area. Continuity, completeness, fairness, objectivity, collaboration, and practicality are some of the common evaluation concepts. Its principles consist of responsibility, pedagogy, integration, and coherence, to be precise. Planning, development, monitoring, efficiency, effectiveness, and a comprehensive program are all evaluated as part of the learning process. According to the object, input, transformation, and output are all included in the learning evaluation. Trainers, trained police, and self-evaluating students are among the topics covered. It consists of tests and non-tests, technically speaking. Examination of Islamic religious subjects in schools must be carried out regularly, comprehensively, and holistically. As a result, Islamic religion teachers must be able to evaluate the progress of their students in Aqliyah, Qolbiyah, and Amaliyah.